2017
DOI: 10.7150/jca.17668
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood lymphocyte-to-monocyte ratio as a prognostic factor in advanced epithelial ovarian cancer: a multicenter retrospective study

Abstract: The lymphocyte-to-monocyte ratio (LMR), as a surrogate marker of systemic inflammation, has been found to be a novel prognostic indicator in various malignancies. Data from 672 advanced epithelial ovarian cancer (EOC) patients treated with neoadjuvant chemotherapy (NAC) followed by debulking surgery were analyzed, and the prognostic value of LMR were evaluated. The optimal cutoff point of LMR in prediction of survival was defined as 3.45 through receiver operating characteristics curve analysis. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…NLR is a composite marker of absolute peripheral neutrophil and lymphocyte counts, and LMR is a composite marker of absolute peripheral lymphocyte and monocytes counts. These cells comprise the total leukocyte count which has previously been shown to be associated with cardiovascular and cancer mortality, as well as allcause mortality [17][18][19][20][21][22]. However, they play a different role in the inflammation and possibly in the pathogenesis of these differing medical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is a composite marker of absolute peripheral neutrophil and lymphocyte counts, and LMR is a composite marker of absolute peripheral lymphocyte and monocytes counts. These cells comprise the total leukocyte count which has previously been shown to be associated with cardiovascular and cancer mortality, as well as allcause mortality [17][18][19][20][21][22]. However, they play a different role in the inflammation and possibly in the pathogenesis of these differing medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among patients with acute myocardial infarction, it has been shown that an increased NLR is a predictor of in-hospital mortality and morbidity [26], and impaired myocardial perfusion after percutaneous coronary angioplasty [27]. Similarly, LMR has been reported to be associated with adverse prognosis in multiple malignancies [22,28] and coronary artery disease [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated monocyte count in peripheral blood has been associated with detrimental outcomes for cancer patients. LMR is calculated as the ratio of ALC and AMC, and it has been proposed as a prognostic or predictive factor associated with survival in various malignancies including ovarian cancers 22 , 23 , 26 , 27 . In EOC with stage I to IV disease, a low LMR is an independent predictor for overall survival (OS) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preoperative NLR and PLR may help distinguish malignant from benign ovarian masses 18 - 20 ; however, there is lack of consensus regarding their value as a screening tool for ovarian cancer 21 . Recently, the LMR, the ratio of absolute neutrophil count (ANC) to the absolute monocyte count (AMC), has been reported to be a predictive factor for survival in early- and advanced-stage epithelial ovarian cancer (EOC) 22 , 23 . However, to the best of our knowledge, there are no published reports on the cut-off LMR value distinguishing malignant from benign ovarian masses.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte / monocyte ratio (LMR),a new indicator of basal inflammatory response, has recently been implicated in many types of malignancy 6,7 Additionally, low LMR levels have been shown to be closely related to the severity of coronary artery disease 8 . Recent studies have revealed low LMR levels after AIS, which was inversely correlated with neurological disability 3 months after AIS 9 .It has been identified that, some of the white blood cell subtypes are associated with the mortality due to cerebrovascular diseases 10 .…”
Section: Introductionmentioning
confidence: 99%